A Centenary of the State Statistical Office - Prokop Závodský; Ondřej Šimpach (Statistika (Prague, Czech Republic), 2019)
In the Austrian part of the Habsburg monarchy, official statistics were controlled by the Vienna central authorities (the Central Statistical Commission, Ministry of Commerce and other ministries) and statistical offices of local authorities in the individual countries (Bohemia, Moravia, Silesia and others), whose competences were very limited. Insufficient cooperation and coordination of activities of these statistical offices had been subject to criticism as well as the lack of general reporting obligations. The Czechoslovakian Act regulating the state statistics approved by the Revolutionary National Assembly, three months after the establishment of a new state centralized statistical service to the Statistical State Council as a Deputy Authority and the State Statistical Office as an executive body, and also enacted general reporting obligations and guarantees of consistent protection of individual data. The current statute of the state statistical service in the Czech Republic is actually based on the same principles as the Act approved a century ago. The paper describes the emergence of Act No. 49/1919 and a long and complicated path leading to its fulfilment. The protracted problem was also the post of the chairman of both statistical authorities and the provision of a suitable object for activity of the State Statistical Office.